Contractility patterns and gastrointestinal movements monitored by a combined magnetic tracking and motility testing unit. Issue 6 (10th December 2021) - Liao, Donghua; Mark, Esben Bolvig; Nedergaard, Rasmus Bach; Wegeberg, Anne‐Marie; Brock, Christina; Krogh, Klaus; Drewes, Asbjørn Mohr
Abstract: Background: Ingestible wireless capsules, including the 3D‐transit magnetic capsule and the wireless motility capsule (WMC), describe gastrointestinal (GI) motility from changes in position or pressure. This study aimed to combine information on contractile events in terms of position (assessed with the 3D‐transit) and change in pressure (assessed with the WMC) throughout the entire GI tract. Methods: The 3D‐transit capsule and WMC were combined into a single‐wireless unit system. Three‐dimensional space‐time coordinates, pressure, and pH data from a pilot case were analyzed as the combined unit passed the GI tract. Two single and three continuous contraction patterns were defined according to pressure changes and quantified through the GI tract. Key results: The combined unit was well tolerated and provided information on contractions throughout the gut. Single contraction patterns with no significant progressive movement of the unit were most prevalent in the stomach and the rectosigmoid colon. During the continuous contraction patterns, the unit moved in an antegrade or retrograde direction. Longer distance and higher velocity were seen during antegrade than during retrograde movements. The motility indices (as measured with WMC) in combined ascending, transverse and descending colon showed a positive linear association ( r = 0.7) to the capsule movements (as measured with 3D‐transit). Conclusions & inferences: The combined system provides synchronous information about movements and gut contractions. These measurements can be used to extract more information from existing recordings and may enhance our understanding of GI motility in health and disease. Abstract : The combined wireless motility capsule and the 3D‐transit unit provides a synchronous assessment of gut contractions and capsule movements when the combined unit traverses through the entire gastrointestinal tract.